Sustainability in Environmental Education: Away from pluralism and towards solutions - Kopnina, Helen (REBRAE, 2014)
Researchers in education for sustainable development have argued that sustainability is not fixed but socially constructed, and that sustainability issues should be represented as a continuous quest rather than indisputable targets that can be anticipated, planned and regulated according to predetermined guidelines. These scholars often doubt that there is one ‘right’ way to be sustainable. Considering the immensity of environmental sustainability challenges, such as climate change, species extinction, and pollution, this article takes a different perspective. The author will argue that without acceptance of unsustainability as a concrete challenge that requires concrete positivistic solutions, the challenge of addressing unsustainable practices becomes unsurmountable. The author will argue that there is a need for clear articulation of 1. What (un)sustainability is; and 2. What the key challenges and causes of (un)sustainability are; and 3. How the sustainability challenges can be meaningfully addressed. This article will outline a number of helpful frameworks that address obstacles to sustainability, ranging from population growth to unsustainable production and consumption practices. In particular, these solutions include investment in family planning policies to counter the effects of overpopulation, and alternative production frameworks, such as Cradle to Cradle, The Blue Economy and Circular Economy that differ from the conventional frameworks such as eco-efficiency, and have the potential to move the quest for sustainability beyond ‘business as usual’. This article will conclude with the broader reflection that without goaloriented critical learning explicitly providing alternative sound models of sustainability, democratic learning may never permit transcendence from unsustainable models. In order to overcome the practical impasse inherent in much of neoliberal education, educators can begin to close ranks and realize that each has valuable strengths that can help in the reconstruction of education for sustainability.